The Simultaneous Effect of Apical Resection Angle and Depth of Retrograde Cavity on Apical Microleakage via Fluid Filtration Method - Sahebi, Safoora; Moazzami, Fariborz; Dehghan, Roya; Ghahramani, Yasamin (Iranian Endodontic Journal, 2019)
Introduction: The goal of apical surgery is to eliminate the root apex, apical lesions and promote tissue repair. In apical surgery, the root is resected at an angle of 45, 60 or 90 degree. In many cases, it is not possible to resect the root at 90-degree bevel and prepare a root-end cavity with 4-mm depth. The aim of this study was to evaluate the simultaneous effect of apical resection angle and depth of the retrograde filling with mineral trioxide aggregate (MTA) on apical microleakage. Methods and Materials: Root ends were resected at 45 degree, 60 degree and 90 degree bevels in 110 extracted human single root permanent teeth. For each apical surgery, root-end cavities were filled with MTA to depths of 2 mm, 3 mm and 4 mm. Root end-filled teeth were mounted in fluid filtration device. The evaluation was conducted after 24-h, 1 week, 1 month, 2 months and 3 months. Each group included 10 samples. Also 20 roots were used as positive and negative control samples, in the negatives the entire root surface was coated with 2 layers of nail varnish and positives were unfilled root-end preparation. Statistical analysis consisted of the Kruskal-Wallis test and Pairwise comparison. Results: There were no significant differences in apical microleakage after 24 h and 1 week in the experimental groups. In the 3rd month, samples with 90° bevel and 4-mm-thick MTA showed significant statistical differences with all samples with 45° and 60° bevels and depths of 2- and 3-mm-thick MTA (P<0.05). Conclusions: This in vitro study showed that when the resection angle is 90°, retrograde depth does not affect microleakage, but resection angles other than 90°, require 4 mm-retrograde depth to be sealed. Keyword: Microleakage; Mineral Trioxide Aggregate; Retrograde Obturation; Root Resection